Supply and Marketing of Local Chicken in the Town of Abeche in Eastern Chad - Adoum, Issa Youssouf; Youssouf, Mopate Logtene; Vounparet, Zeuh; Djalal, Ardjoun Khalil; Oumar, Bada Algom; Mustapha, Adam Bakhit (Pakistan Journal of Nutrition, 2014)
The study characterized the supply and marketing of local chicken in the markets of the city of Abeche. It involved 38 traders including 23 wholesalers retailers, 13 retailers and two hawkers selling in five poultry markets located in the 2nd, 3rd and 6th districts of the city. Traders, aged 36.21±10.9 years, are mostly Muslims (100%) of whom 52.62% schooled and 47.36% illiterate who started their activities between the 1990s and 2000s (89.47%). Wholesalers and retailers get their supply especially in the regions of Ouaddai, Wadi Fira and Sila (97.36%). As for hawkers (5.26%), they get their supply from the selling markets in Abeche. Transportation is done by trucks (50.01%), carts (34.21%) and motorcycles (32.21%). Packaging consists mostly of cages (89.5%). Of the 156 birds lost during transportation, chickens constitute 86.5% of the number and pigeons 13.5%. These losses are estimated to the amount of 395,283 FCFA. The major customers are housewives (40%), restaurant’s owners and braisers at drinking spots (60%). The average selling prices are 2,926 FCFA/chicken, 2,241 FCFA per guinea fowl, 8,125 FCFA per duck and 646 FCFA/pigeon. The average gross margin on less sold ducks is higher (p<0.001) than that which realized on the other species. Organizing the actors, allocating some facilities at the markets as well as improving storage and transport will allow for a better supply of local chickens in the city.